An ultrasensitive flow cytometric immunoassay based on bead surface-initiated template-free DNA extension. Issue 32 (30th July 2018) - Zhu, Liping; Chen, Desheng; Lu, Xiaohui; Qi, Yan; He, Pan; Liu, Chenghui; Li, Zhengping
Abstract : An ultrasensitive flow cytometric immunoassay (TdT-FCI) is developed based on bead surface-initiated template-free DNA extension. Abstract : Proteins lack the duplication mechanism like nucleic acids, so the connection of immunoassays with effective nucleic acid amplification techniques has become a powerful way for the detection of trace protein biomarkers in biological fluids. However, such immunoassays generally suffer from rather stringent DNA sequence design and complicated operations. Herein, we propose a simple but highly sensitive flow cytometric immunoassay (FCI) by employing on-bead terminal deoxynucleotidyl transferase (TdT)-initiated template-free DNA extension as an effective signal amplification pathway (TdT-FCI), and gold nanoparticles (AuNPs) co-functionalized with both the detection antibody and a 3′-OH oligonucleotide (ODN) as the transducer to bridge the immunoassay and subsequent TdT-mediated DNA amplification. The target antigen can sandwich with the capture antibody immobilized on the magnetic beads (MBs) and the detection antibody on the AuNPs to bring a lot of ODNs onto the surface of MBs. Each ODN on the MBs can be effectively elongated by TdT in a template-free manner to produce a long poly(T) tail, which will then bind to many 6-carboxyfluorescein (FAM)-labeled poly(A)25. Since each AuNP can carry multiple ODNs and each extended ODN can ultimately capture numerous FAM-poly(A)25, efficiently amplified fluorophore accumulation on the MBs can be achieved. The fluorescent MBs can be individually interrogated with a flow cytometer and thus quantitative analysis of the target antigen can be realized. Coupled with the powerful flow cytometry analysis, the simple but efficient TdT-based signal amplification mechanism has pushed the detection limit of prostate specific antigen (PSA) down to a low level of 0.5 pg mL −1 . Furthermore, based on an elegant bead size-encoding principle, we have further advanced the TdT-FCI for multiplexed antigen detection in a single reaction. Sharing the unique merits of simple design and operation, efficient signal amplification, powerful signal readout and the capability for multiplexed analysis, this TdT-FCI provides a versatile tool for detecting trace antigen biomarkers towards clinical diagnosis as well as prognosis.